2011
DOI: 10.1016/j.ijgo.2010.09.009
|View full text |Cite
|
Sign up to set email alerts
|

Randomized study of vaginal and neonatal cleansing with 1% chlorhexidine

Abstract: Use of 1% CHX is safe for neonates, well tolerated by laboring mothers, and effective in treating vaginal infections during labor. A randomized controlled trial using 1% CHX and powered for a reduction in neonatal septic mortality is justified based on these data.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 22 publications
0
14
0
1
Order By: Relevance
“…Characteristics of included studies are detailed in Table 1 , including potential confounding factors. Only two of the studies [ 27 , 40 ] were undertaken in low resource settings (Table 1 ).
Fig.
…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Characteristics of included studies are detailed in Table 1 , including potential confounding factors. Only two of the studies [ 27 , 40 ] were undertaken in low resource settings (Table 1 ).
Fig.
…”
Section: Resultsmentioning
confidence: 99%
“…2 ). Two studies [ 21 , 27 ] investigated the effect of chlorhexidine on maternal colonization, including 53 participants in the intervention group and 51 in the control group, which also showed no significant difference on colonization (Relative risk (RR) 0.61, 95% confidence intervals (CI) 0.05-8.08) Heterogeneity – I 2 = 93%, P < 0.001.
Fig.
…”
Section: Resultsmentioning
confidence: 99%
“…However, safety and feasibility of home-based parenteral antibiotic therapy must be carefully assessed before it can be recommended as an alternative to facility-based care. The systematic review also concluded that in situations without available hospitalbased care, the combination of clean birth practices [25] and prompt initiation of oral antibiotic therapy for potentially serious neonatal infections were likely to be of substantial benefit. The most effective and safe enteral antibiotics identified included co-trimoxazole, secondgeneration cephalosporins, ciprofloxacin, amoxicillin, and combined amoxicillin-clavulanic acid.…”
Section: Discussionmentioning
confidence: 99%
“…For patients who are allergic, diluted 4% chlorhexidine gluconate is used. 9 The staff member performing the prep uses cotton tip applicators with iodine paint to clean the umbilicus of detritus (ie, debris). Next, each foam sponge is dipped in the scrub solution to vigorously scrub, in sequence, the abdomen, top third of the thighs, perineum, and vulva, and then the vaginal interior up to and around the cervix; the sponge is discarded after the anus is swabbed (Figure 1).…”
Section: Methodsmentioning
confidence: 99%
“…First, it is confirmed that the patient is not allergic to external iodine preparations. For patients who are allergic, diluted 4% chlorhexidine gluconate is used 9 . The staff member performing the prep uses cotton tip applicators with iodine paint to clean the umbilicus of detritus (ie, debris).…”
Section: Description Of the Problemmentioning
confidence: 99%